SARS‐CoV‐2 Omicron variant: Why global communities should take it seriously?. Issue 5 (19th April 2022) - Rahmani, Shayan; Rezaei, Nima
Abstract: Introduction: In November 26th, 2021 a new strain of SARS‐CoV‐2 was designated by the World Health Organization as a variant of concern and named Omicron. The news broadcasted a global wave of panic and anxiety while many, like 2 years ago, were making themselves ready for the holiday season. After almost a month of its designation, countries from all 6 continents have been reported Omicron from their genomic sequences. This triggered an international alarm about a new era in the Covid‐19 pandemic, where despite the vast amount of vaccinations, a surge in new cases and hospitalizations are reported from all over the world. Methods: Scientific literature published from November 26, 2021 to March 21, 2022 have been searched and retrieved by using "SARS‐COV‐2", "Omicron", "B.1.1.529", "Covid‐19", and "global community" keywords from "PubMed", "Web o "Google Scholar", and "MedRxiv" databases. Results: Omicron have been evolved to spread faster than previous variants of concern, but it infects people lesser than other variants, Delta for example. Omicron can also escape vaccine‐induced immunity more than previous SARS‐CoV‐2 variants. Discussion: Despite possible lower lethal risks than previous strains, Omicron may provide populations with a higher community transmission and a higher hospitalization load, which potentially overwhelm already exhausted health care systems. Therefore, we need to get used to the "New Normal" and maintain health recommendations to help decrease spreading of the virus and buy more time for the scientists to dive deeper into potential ways of tackling Covid‐19, more than ever.